Characterisation of Saw Dust Ash – Quarry Dust Bituminous Concrete - Kenneth Miebaka Oba; Emmanuel Ledesi Tigbara (International Journal of Engineering and Management Research, 2021)
This study evaluates usefulness of Quarry Dust and Saw Dust Ashas mineral fillers in a bituminous concrete in order to reduce cost and encourage reuse of waste materials in the environment. Bituminous concrete blends were generated with 4% Quarry Dust and 4% Saw Dust Ash replacements of aggregates. The binder contents were 3, 3.5, 4, 4.5 and 5% for a 60/70 penetration grade bituminous binder. Briquette specimens were formed using the five different bituminous concrete blends. Standard laboratory experiments were conducted on the aggregates, Quarry Dust, Saw Dust Ash, bituminous binder and bituminous concrete specimens based on the relevant codes and standards. The Marshall method was used for the bituminous concrete design procedure. The optimum binder content was found to be 4.88% using the standard Marshall curves. At optimum binder content, using 4% design air void for medium traffic and maximum aggregate of 10mm, the Stability, Flow, VMA and VFA were 8.15kN, 8.28(0.25mm), 15.22% and 74.2% respectively. These were found to have passed the Asphalt Institute design criteria.